Self-efficacy in volleyball: What has been evaluated? A systematic review - Machado, Thais do Amaral; Balaguer, Isabel; Paes, Mayara Juliana; Jungles Fernandes, Gabriel; Facco Stefanello, Joice Mara (Cuadernos de Psicología del Deporte, 2018)
Self-efficacy in sport has been the purpose of study in different modalities, among them the volleyball. The aim of the study was to verify by means of a systematic review what has been evaluated volleyball self-efficacy. The databases APA, Bireme, Eric, Science Direct, Pubmed and Scopus were used to carry out the searches. After the research, the articles were selected, using the inclusion and exclusion criteria, resulting in 7 articles by the theme. The result points a absence of clarity in the instruments for assessing self-efficacy in volleyball with respect to what they intend to measure in relation to technical, tactical, physical or psychological attributes. In addition, few articles have pointed the psychometric properties of the instruments used in the research, which implies, in practical terms, inaccurate results, hindering the reproducibility of the studies. Therefore, it is suggested that specific instruments for the modality should be developed which present the statistical procedures used in order to obtain reliable results.